Synthesis and properties of poly(propylene) and poly(hexamethylene adipamide) ion exchange fibres - Whelan, M. P.(Michael Patrick) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1987.